2009
DOI: 10.26719/2009.15.2.443
|View full text |Cite
|
Sign up to set email alerts
|

Injection safety at primary health care level in south-western Saudi Arabia

Abstract: Sécurité des injections au niveau des soins de santé primaires dans le sud-ouest de l'Arabie saoudite RÉSUMÉ Dans le cadre d'une étude sur la sécurité des injections dans le district de santé d'Abha (Arabie saoudite), des données ont été recueillies auprès de 47 médecins et de 85 infirmières dans 24 centres de soins de santé primaires, sur la base d'une grille d'observation et d'un questionnaire d'entretien. Tous les centres utilisaient des seringues jetables en emballage individuel et des récipients imperfora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
14
4
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 7 publications
6
14
4
1
Order By: Relevance
“…30 (100.0%) were females; it was dissimilar from the study of A. A. Mahafouz et al 11 study in which 35.5% were females.…”
Section: Resultscontrasting
confidence: 61%
See 2 more Smart Citations
“…30 (100.0%) were females; it was dissimilar from the study of A. A. Mahafouz et al 11 study in which 35.5% were females.…”
Section: Resultscontrasting
confidence: 61%
“…A. A. Mahfouz et al 11 stated that 11.3% providers were bending the needle before disposal while in this study this was quite high i.e. 14 (46.6%) providers bended the needle before the disposal which is a negative part of the injection practices.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…Out of 15 sub centres, 10 sub centres practices outside treatment along with PHC and BPHC. Similar study done by Mahfouz et al, in south-western Saudi Arabia showed that all the rural and urban health facilities had provision of professional company service for waste disposal [12]. Another study among PHC level worker in Nepal by Gyawali S et al, showed that in 80% case open burning was the main method for waste disposal [13].…”
Section: Discussionmentioning
confidence: 62%
“…The needle recapping in current study was less when compared with a Nigerian study [19] that 30.4% of health workers recap needles. Mahfouz [20] and Hutin [21] reported that needle recapping with other factors are the major causes of injury among health workers.…”
Section: Open Access Ppmentioning
confidence: 99%